A Development and evaluation of a 3D electromagnetic field simulation tool for aviation communication engineering education - Fatmawati Sabur; Heru Prasetyo; Mulyadi Nur; Kurniaty Atmia; Supriyadi Supriyadi; Devi Dwi Purwanto; Slamet Winardi; Arsyen Pratama Parrangan; Che Zalina Zulkifli (Jurnal Pendidikan Vokasi, 2026)
This study addresses a learning gap in Aviation Communication Engineering education, where electromagnetic field concepts are highly abstract and difficult to understand through conventional teaching methods. Existing instructional media provide limited interactive and contextualized visualizations of electric and magnetic field phenomena, resulting in low levels of students’ conceptual understanding. The study employed a Research and Development (R&D) methodology based on the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model. Subject matter experts and media experts evaluated the application in terms of content validity, interface design, and interactivity. The primary outcome was the development of a web-based three-dimensional (3D) electromagnetic field simulation to support learning in aviation communication engineering. Its effectiveness was subsequently evaluated using a quasi-experimental pre-test–post-test control-group design involving 30 students assigned to experimental and control groups. The experimental group used the web-based 3D simulation developed with Python and Three.js, whereas the control group received conventional instruction. Data were analyzed using paired-samples t-tests, Cohen’s d effect size, and 95% confidence intervals. The results revealed significant improvements in both groups (p < 0.05), with the experimental group demonstrating greater learning gains (M = 23.3; from 63.2 to 86.5; t = −73.06) than the control group (M = 11.3; from 62.8 to 74.1; t = −48.79). Effect size analysis indicated a very large educational impact (Cohen’s d ≈ 5.85), while the confidence intervals showed no overlap between groups, supporting the robustness of the observed differences. The findings suggest that 3D simulation-based learning is more effective than conventional instruction in enhancing students’ conceptual understanding of electromagnetic field concepts. The study also provides empirical support for the Cognitive Theory of Multimedia Learning and Cognitive Load Theory in the context of vocational aviation education.